2015
DOI: 10.1089/dia.2014.0327
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Basal Glucose and Postprandial Glucose Concentrations to Hemoglobin A1c in the Newly Diagnosed Patients with Type 2 Diabetes—The Preliminary Study

Abstract: Objective: The aim of this preliminary study is to investigate contributions of basal glucose (BG) and postprandial glucose (PPG) increments to overall hyperglycemia in newly diagnosed patients with type 2 diabetes mellitus (T2DM). Research Design and Methods: We evaluated the relative contributions of BG and PPG to overall hyperglycemia in 59 newly diagnosed T2DM patients according to BG baseline value of 6.1 mmol/L and 24-h glucose profiles of normal glucose tolerance (NGT) subjects obtained by continuous gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 13 publications
(6 reference statements)
5
26
0
Order By: Relevance
“…In summary, the relative contribution of PPG as compared with FPG is high in those with the lowest HbA1c values, both in people on oral agents and as now reported by Kang et al 1 also in newly diagnosed patients. But taking all the available evidence together, it is not surprising that treatment guidelines do not recommend specific targeting of PPG values in those with lower HbA1c values.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…In summary, the relative contribution of PPG as compared with FPG is high in those with the lowest HbA1c values, both in people on oral agents and as now reported by Kang et al 1 also in newly diagnosed patients. But taking all the available evidence together, it is not surprising that treatment guidelines do not recommend specific targeting of PPG values in those with lower HbA1c values.…”
supporting
confidence: 70%
“…I n this issue of Diabetes Technology & Therapeutics, Kang et al 1 report on the relative contributions of fasting plasma glucose (FPG) and postprandial glucose (PPG) to overall glycemia as a function of different hemoglobin A1c (HbA1c) ranges in untreated, newly diagnosed patients with type 2 diabetes. Using continuous glucose monitoring, they found that PPG accounted for 77% of overall hyperglycemia in those with an HbA1c level below 7%, but only 23% in those with an HbA1c level above 9%.…”
mentioning
confidence: 99%
“…This added further information on the findings of previous studies, which included either drug‐naïve or OAD‐treated type 2 diabetes among Caucasians and East Asians only, except Kikuchi et al . who also recruited those taking basal insulin. In addition, Wang et al .…”
Section: Discussionmentioning
confidence: 95%
“…with a predominance of PPH at lower HbA 1c levels were reported. One of the main differences of these studies was on the HbA 1c threshold in which the shift of FH and PPH predominance occurred. Wang et al .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation